Using a Simple Prescription Gap to Determine Warfarin Discontinuation Can Lead to Substantial Misclassification - Lin, Kueiyu Joshua; Schneeweiss, Sebastian; Pawar, Ajinkya; Singer, Daniel E.; Liu, Jun; Gagne, Joshua J. (Thrombosis and Haemostasis, 2021)
Background Warfarin remains widely used and a key comparator in studies of other direct oral anticoagulants. As longer-than-needed warfarin prescriptions are often provided to allow for dosing adjustments according to international normalized ratios (INRs), the common practice of using a short allowable gap between dispensings to define warfarin discontinuation may lead to substantial misclassification of warfarin exposure. We aimed to quantify such misclassification and determine the optimal algorithm to define warfarin discontinuation.Methods We linked Medicare claims data from 2007 to 2014 with a multicenter electronic health records system. The study cohort comprised patients ≥65 years with atrial fibrillation and venous thromboembolism initiating warfarin. We compared results when defining warfarin discontinuation by (1) different gaps (3, 7, 14, 30, and 60 days) between dispensings and (2) having a gap ≤60 days or bridging larger gaps if there was INR ordering at least every 42 days (60_INR). Discontinuation was considered misclassified if there was an INR ≥2 within 7 days after the discontinuation date.Results Among 3,229 patients, a shorter gap resulted in a shorter mean follow-up time (82, 95, 117, 159, 196, and 259 days for gaps of 3, 7, 14, 30, 60, and 60_INR, respectively; p < 0.001). Incorporating INR (60_INR) can reduce misclassification of warfarin discontinuation from 68 to 4% (p < 0.001). The on-treatment risk estimation of clinical endpoints varied significantly by discontinuation definitions.Conclusion Using a short gap between warfarin dispensings to define discontinuation may lead to substantial misclassification, which can be improved by incorporating intervening INR codes.
Keywords: warfarin discontinuation; stroke prevention; exposure misclassification